Association Between Acanthosis Nigricans and Cardiometabolic Risk Among Overweight and Obese Patients Admitted to the Teaching Hospital Jaffna - Kethuja, A.; Kumanan, T. (The Jaffna Medical Association, 2024)
Acanthosis nigricans is strongly associated with obesity and insulin resistance. This cross-sectional analytical hospital-based study is conducted to access the Association Between Acanthosis Nigricans (AN) and cardiometabolic risk among overweight and obese patients aged 18 and above admitted to medical wards of Teaching Hospital Jaffna. Data were entered and analysed using Statistical Packages for social sciences (SPSS) version 21. Out of the 230 overweight and obese patients 74.8% had AN. Patients with AN had a higher mean BMI value of 29.65 suggesting that significant percentage of patients with AN are obese rather than being overweight. Higher prevalence of AN among females were noted. Presence of skin tags revealed an important association with AN. Most of the participants had central obesity regardless whether they were overweight or obese. Even though statistically insignificant, individuals with AN had increased likelihood of having metabolic syndrome and associated with smokers. A significant association between Sagittal Abdominal Diameter(SAD) and presence of AN were noted. The mean of sagittal circumference in those with AN and those without respectively are 22.02 and 20.43. In conclusion AN is strongly associated with higher BMI (Obesity), higher waist circumference and higher sagittal abdominal diameter and metabolic syndrome and smoking demonstrated a strong association with AN.